2022
DOI: 10.3390/agriculture12091420
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Comparative Analysis of Two Subtypes of Cofilin Family on Cattle Myoblasts Differentiation

Abstract: Agricultural meat composition and quality are not independent of the effects of skeletal muscle growth and development in animals. Cofilin is distributed extensively in muscle and non-muscle cells, and its function is tightly regulated in the cell. Cofilin has two variants in mammals, cofilin-1 (CFL1, non-muscle type) and cofilin-2 (CFL2, muscle type), and has a dual function on skeletal muscle fibers. Our study examined the expression pattern of CFL1 and CFL2 in different fetal bovine, calf, and adult cattle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…NAT transcript sequences partially or completely overlap and complement mRNA, promoter or regulatory regions of coding genes and participate in gene expression regulation at the transcriptional and posttranscriptional levels [ 40 ]. CFL1 and CFL2 play an important role in the growth and differentiation of skeletal muscle [ 18 ]. We predicted that the sequence of CFL1-AS1 can complement the partial sequences of CFL1 and CFL2, suggesting that CFL1-AS1 May regulate the development and differentiation of skeletal muscle by affecting the expression of CFL1 and CFL2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAT transcript sequences partially or completely overlap and complement mRNA, promoter or regulatory regions of coding genes and participate in gene expression regulation at the transcriptional and posttranscriptional levels [ 40 ]. CFL1 and CFL2 play an important role in the growth and differentiation of skeletal muscle [ 18 ]. We predicted that the sequence of CFL1-AS1 can complement the partial sequences of CFL1 and CFL2, suggesting that CFL1-AS1 May regulate the development and differentiation of skeletal muscle by affecting the expression of CFL1 and CFL2.…”
Section: Discussionmentioning
confidence: 99%
“…Both the CFL2 gene and CFL1-AS1 parent gene CFL1 are closely related to muscle growth and development and play an important role in normal muscle function and regeneration. Previous studies have shown that the CFL1 and CFL2 genes are specifically expressed in different growth and development stages of bovine muscle and show opposite expression patterns during muscle cell differentiation [ 17 , 18 ]. RNAhybrid analysis identified a miR-125b binding site on CFL1-AS1, and studies have shown that miR-125b can regulate the proliferation and differentiation of myoblasts [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In future production practices, it is important to pay special attention to mutations associated with abnormalities in dairy-cattle populations, such as defects in bovine leukocyte adhesion, complex vertebral malformations, and short spinal or short spinal lethal syndrome, as representative examples of inherited diseases [8]. Meanwhile, two variants of cofilin, cofilin-1 (CFL1, non-muscular type) and cofilin-2 (CFL2, muscular type), have been found in mammals, with a dual function on skeletal muscle fibers [9]. The acute phase response (APR) is a non-specific systemic response in which acute phase protein (APP) production changes.…”
mentioning
confidence: 99%